In Vitro toxicity of oil extracted from neem seeds collected from different locations across savanna agro-ecological zones of Nigeria on seed and soil-borne pathogens of cowpea (Vigna unguiculata L. Walp) (2010)
Graded extracts of neem seed oil extracted across the savanna agro-ecological zones (AEZs) of Nigeria were tested on mycelial growth of Colletotrichum capsici and Macrophomina phaseolina of cowpea in Nigeria. Minimum inhibition concentrations (MIC) and effectiveness levels of oil from AEZs were determined. Data were subject to ANOVA. Biplot was employed to access variation and interactions among the AEZs. Across the AEZs, fungitoxicity, MIC and effectiveness level varies; concentrations of 0.1 and 1.0% reduced the growth of C. capsici, while M. phaseolina was reduced at 10% concentration. On M. phaseolina, neem oil extracted from Ilorin, Ogbomosho (derived savanna) and Mokwa (southern guinea savanna) performed similarly, while a strong positive association existed between Ogbomosho (derived savanna) and Hadejia (Sahel savanna) samples. On C. capsici, samples from Bida (southern guinea savanna) and Ilorin (Derived savanna) were similar. This result could be a possible link between ecology, biodiversity and toxic principles in plant materials.